Online Brand Community Components in Gadgets Industry, Thailand - Oranich Kumgliang; Anon Khamwon; Rathakarn Buasri (ADI Journal on Recent Innovation, 2022)
Current global businesses focus on interacting with customers by creating an online brand community to create market venues to be more successful. However, creating a venue for brands comes with a high challenge in terms of managing the media and the activities to be unique and draw in more customers. This research aims to study and confirm the online brand community components in gadget products, which are the products that many people talk about and exchange their experiences in terms of the brands. To understand the major component of creating an online community, the researcher collected the data using an online questionnaire with 400 people who had purchased electronic accessories or gadgets through an e-commerce channel. The result from the analysis of the confirmation components revealed that the online brand communities consist of three following components: the feeling of inclusiveness within the communities, shared norms and traditions, and the feeling of responsibility towards the communities.